Analysis of Adaptive Olaparib Resistance Effects on Cisplatin Sensitivity in Triple Negative Breast Cancer Cells - Gajan, Ambikai; Sarma, Ashapurna; Kim, Seongho; Gurdziel, Katherine; Wu, Gen Sheng; Shekhar, Malathy P. (Frontiers in Oncology, 2021)
Poly-(ADP)-ribose polymerase inhibitors (PARPi) and platinum-based drugs are promising therapies for triple negative breast cancers (TNBC) with BRCA1 or BRCA2 loss. PARPi(s) show better efficacies when combined with platinum-based therapy, however, acquisition of PARPi resistance has been linked with co-resistance to platinum-based drugs. Here, we show that TNBCs with constitutively hyperactivated PARP-1 display greater tolerances for the PARPi olaparib and cisplatin, and respond synergistically to olaparib/cisplatin combinations with increased cytotoxicity. Regardless of BRCA1 and PARP-1 activity status, upon gaining olaparib resistance (OlaR), OlaR MDA-MB-468 (BRCA1 wild-type) and SUM1315 (BRCA1 mutant) TNBC cells retain cisplatin sensitivities of their isogenic parental counterparts. OlaR TNBC cells express decreased levels of PARP-1 and Pol η, a translesion-synthesis polymerase important in platinum-induced interstrand crosslink repair. Although native RAD51 recombinase levels are unaffected, anti-RAD51 immunoreactive low molecular weight sbands are exclusively detected in OlaR cells. Despite normal BRCA1, RAD51 foci formation/recruitment to double-strand breaks are impaired in OlaR MDA-MB-468 cells, suggesting homologous-recombination impairment. RNA-seq and pathway analysis of cisplatin-affected genes revealed enrichment of G2/M cell cycle regulation and DNA repair pathways in parental and OlaR MDA-MB-468 cells whereas parental and OlaR SUM1315 cells showed enrichment of inflammatory stress response pathways associated with TNFR1/2, TWEAK and IL-17 signaling. These data show that TNBC models with wild type versus mutant BRCA1 exhibit differences in CDDP-induced cellular response pathways, however, the CDDP-induced signaling responses remain stable across the isogenic models of OlaR from the same lineage. These data also show that adaptive OlaR does not automatically promote cisplatin resistance, implicating the potential benefit of platinum-based therapy for OlaR TNBCs.